Disruption of BASIGIN decreases lactic acid export and sensitizes non-small cell lung cancer to biguanides independently of the LKB1 status - Granja, Sara Costa (2015)
Most cancers rely on aerobic glycolysis to generate energy and metabolic intermediates. To maintain a high glycolytic rate, cells must efficiently export lactic acid through the proton-coupled monocarboxylate transporters (MCT1/4). These transporters require a chaperone, CD147/BASIGIN (BSG) for trafficking to the plasma membrane and function. To validate the key role of these transporters in lung cancer, we first analysed the expression of MCT1/4 and BSG in 50 non-small lung cancer (NSCLC) cases. These proteins were specifically upregulated in tumour tissues. We then disrupted BSG in three NSCLC cell lines (A549, H1975 and H292) via ‘Zinc-Finger Nucleases’. The three homozygous BSG-/- cell lines displayed a low MCT activity (10- to 5-fold reduction, for MCT1 and MCT4, respectively) compared to wild-type cells. Consequently, the rate of glycolysis, compared to the wild-type counterpart, was reduced by 2.0- to 3.5-fold, whereas the rate of respiration was stimulated in BSG-/- cell lines. Both wild-type and BSG-null cells were extremely sensitive to the mitochondria inhibitor metformin/ phenformin in normoxia. However, only BSG-null cells, independently of their LKB1 status, remained sensitive to biguanides in hypoxia in vitro and tumour growth in nude mice. Our results demonstrate that inhibiting glycolysis by targeting lactic acid export sensitizes NSCLC to phenformin.